Monitored Business and Surveillance in a Time of Big Data - Bloom, Peter (Pluto Press, 2019)
This book explores a central contradiction of 21st century economy and society: the more morally and politically unaccountable capitalism and capitalists are, the more accountable the mass majority of its subjects must become. The technocratic ideology and surveillance culture of our modern marketized societies hides a deeper reality of a free market that is unmanageable and a corporate elite whose actions cannot be traced let alone regulated. This work highlights the paradoxical way an often disjointed and unjustifiable modern neoliberalism persists through subjecting individuals and communities to a wide range of technical and ethical 'accounting' in all areas of contemporary life. These pervasive practices of monitoring and codifying everything and everyone mask how at its heart this system and its elites remain socially uncontrollable and ethically out of control.